The Endophytic Strain ZS-3 Enhances Salt Tolerance in Arabidopsis thaliana by Regulating Photosynthesis, Osmotic Stress, and Ion Homeostasis and Inducing Systemic Tolerance - Shi, Li-Na; Lu, Lan-Xiang; Ye, Jian-Ren; Shi, Hui-Min (Frontiers in Plant Science, 2022)
Soil salinity is one of the main factors limiting agricultural development worldwide and has an adverse effect on plant growth and yield. To date, plant growth-promoting rhizobacteria (PGPR) are considered one of the most promising eco-friendly strategies for improving saline soils. The bacterium Bacillus megaterium ZS-3 is an excellent PGPR strain that induces growth promotion as well as biotic stress resistance and tolerance to abiotic stress in a broad range of host plants. In this study, the potential mechanisms of protection against salinity stress by B. megaterium ZS-3 in Arabidopsis thaliana were explored. Regulation by ZS-3 improved growth in A. thaliana under severe saline conditions. The results showed that ZS-3 treatment significantly increased the biomass, chlorophyll content and carotenoid content of A. thaliana. Compared to the control, the leaf area and total fresh weight of plants inoculated with ZS-3 increased by 245% and 271%, respectively; the chlorophyll a, chlorophyll b and carotenoid contents increased by 335%, 146% and 372%, respectively, under salt stress. Physiological and biochemical tests showed that ZS-3 regulated the content of osmotic substances in plants under salt stress. Compared to the control, the soluble sugar content of the ZS-3-treated group was significantly increased by 288%, while the proline content was significantly reduced by 41.43%. Quantification of Na+ and K+ contents showed that ZS-3 treatment significantly reduced Na+ accumulation and increased the K+/Na+ ratio in plants. ZS-3 also isolated Na+ in vesicles by upregulating NHX1 and AVP1 expression while limiting Na+ uptake by downregulating HKT1, which protected against Na+ toxicity. Higher levels of peroxidase and catalase activity and reduced glutathione were detected in plants inoculated with ZS-3 compared to those in uninoculated plants. In addition, it was revealed that ZS-3 activates salicylic acid (NPR1 and PR1) and jasmonic acid/ethylene (AOS, LOX2, PDF1.2, and ERF1) signaling pathways to induce systemic tolerance, thereby inducing salt tolerance in plants. In conclusion, the results of this study indicate that ZS-3 has the potential to act as an environmentally friendly salt tolerance inducer that can promote plant growth in salt-stressed environments.